2013
DOI: 10.1370/afm.1432
|View full text |Cite
|
Sign up to set email alerts
|

Physician Assistants in Primary Care: Trends and Characteristics

Abstract: PURPOSE Physician assistants (PAs) have made major contributions to the primary care workforce. Since the mid-1990s, however, the percentage of PAs working in primary care has declined. The purpose of this study was to identify demographic characteristics associated with PAs who practice in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 13 publications
(14 reference statements)
1
13
1
Order By: Relevance
“…11,14 PA practice patterns refl ect physician practice, with more women practicing in primary care specialties. 15 Unfortunately, analysis of the different characteristics of female and male PAs is lacking due to a limited number of robust data sets, an issue that should promptly be addressed on a national level.…”
Section: Women Leadership and The Culture Of Medicinementioning
confidence: 99%
“…11,14 PA practice patterns refl ect physician practice, with more women practicing in primary care specialties. 15 Unfortunately, analysis of the different characteristics of female and male PAs is lacking due to a limited number of robust data sets, an issue that should promptly be addressed on a national level.…”
Section: Women Leadership and The Culture Of Medicinementioning
confidence: 99%
“…Multiple studies have compared the scope of patient care services provided by physician assistants and physicians in primary care settings and have concluded that physician assistants can perform 85% to 90% of services traditionally provided by primary care physicians (Hooker & Everett, 2012). Physician assistants practicing in primary care are more likely to be female, older, and Hispanic (Coplan, et al, 2013). ◆ In 2010 and 2011, the rate of nurse practitioners was significantly higher for Whites than for other racial groups (Figure 9.6).…”
Section: Health System Infrastructurementioning
confidence: 99%
“…1 Perhaps more important is the duration in time. But how willing are Americans to accept that change?…”
Section: Patients Like Physician Assistants and Nurse Practitioners Amentioning
confidence: 99%